Limites e fronteiras no evangelho de Mateus - Rodrigues, Elisa (2007)
The Gospel of Matthew makes up the set of the New Testament synoptics and was written in the second half of the 1st century CE. Although the place of origin is uncertain, the generally accepted hypothesis is that it was produced in the vicinity of Antioch in Syria, around the 90's. This research is based on the exegesis of Pericopes 5:27-32, 18 :6-9 and 19:9-12 where we find the treatment of topics such as adultery, fornication and castrations. The content of the pericopes is normative and indicates guidelines for the behavior of the audience gathered around the document. We understand that the authorship of the gospel sought to establish its social identity through the imposition of limits and religious boundaries taken from the Torah, reinterpreted by Jesus of Nazareth and laboriously selected and compiled by gospel authorship. It was necessary to write material that would protect the principles of Jewish tradition and avoid the undesirable 'mixture' with the traditions and customs of Rome. Although the Matean group did not intend to do without Judaism, this movement was inevitable as the Gentiles adhered to the Christian faith. In Matthew's writing, therefore, expressions of Jewish belonging and symbolisms of Hellenic culture are recognized. These are intertexts, ancestral memories and mythical images that together were used as rhetorical techniques aimed at building the identity of the audience composed of Jews, Hellenized Jews and Gentiles (AU).